O ensino de controladoria em Programas de Pós-Graduação stricto sensu em Contabilidade no sul e sudeste do Brasil: uma investigação na percepção discente - Kremer, Jhessica Tamara (2018)
The central problem of this research is that Controllership stands out as a professional activity demanded by the organizations and one of the most coveted by professionals. This profession demands increasingly more versatility, varied knowledge and a series of characteristics (Araújo, 2011), so that the controller needs to know the entire organization and its various areas, because business success depends on the success of the several areas together (Boff, Beuren, & Guerreiro, 2008). In this sense, this work is justified by offering informational subsidies so that the agents of the education can propose improvements, because, in front of the relevance of the subject of control, that is, the study of the Controllership as an area of knowledge discussed and presented in postgraduate programs it is essential to provide a reflection of what is taught in classrooms, to provide educators better conditions when designing their teaching plan (Rodrigues & Amaral, 2006). Thus, the question arises: How is the teaching of Controllership in the stricto sensu postgraduate programs in Accounting in the South and Southeast of Brazil in student‟s perceptions? Faced with this questioning, the objective was to understand how the teaching of Controllership in the stricto sensu postgraduate programs in Accounting in the South and Southeast of Brazil in student‟s perceptions is constituted. Through the qualitative approach, the content analysis method was used in interviews with the students of the Controllership discipline, carried out from August to December, in 2018. The construct teaching and learning process were analyzed through the categories of professor analysis, content and teaching methods. It was verified that the teaching of Controllership is composed of professors who have competences capable of influencing the teaching and learning process, are: organizational experiencing, academic experience, pedagogical practice, mastery of content and effectiveness. As well as professors who adopt the reflective perspective being flexible for the discussion of the knowledge of the controller in the classroom and promoting in the students the autonomy to search for the learning of this knowledge. The teaching of Controllership is composed of contents of a more specific approach to accounting and not an interdisciplinary and multidisciplinary approach, these contents are not applied by the students yet, but these have active assimilation about the contents learned, especially in the organizational environment, however, in the personal and social environment this assimilation still seems timid, which may be due to the predominant approach of specific knowledge that provides a more isolated assimilation. Controlling instruction consists of teaching methods that promote reflexivity and student criticality, especially because students have practiced criticality by analyzing the materials passed from the professor for the previous preparation for the discussions, and by having to search for complementary literatures appropriate. The reflexivity has been present because the students report that the student has to prepare in advance in an intense way, which demands of this reflection, besides that the own exchanges of ideas during the discussions provide the acquisition of reflexivity.